1992
DOI: 10.2527/1992.701178x
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for assessing zinc bioavailability: efficacy estimates for zinc-methionine, zinc sulfate, and zinc oxide

Abstract: The bioavailability of zinc-methionine (ZnMET) was compared to that of feed-grade ZnSO4.H2O using three different diets: purified (crystalline amino acid [AA]), semipurified (soy isolate), and complex (corn-soybean [C-SBM]) diet. With the Zn-deficient purified or semipurified diet, weight gain and tibia Zn responded linearly to both ZnSO4.H2O and ZnMET supplementation. Common-intercept, multiple linear regression indicated differences in Zn bioavailability between ZnMET and ZnSO4.H2O for both diets as indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
285
4
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(325 citation statements)
references
References 0 publications
16
285
4
9
Order By: Relevance
“…Recent research on organic minerals proved that chelate minerals can be more effectively absorbed in the intestines than inorganic oxide and sulfate (Wedekind et al 1992;Aoyagi and Baker 1993). Accordingly, chelated Fe, especially Fe-Gly, has been used more frequently as the Fe fortification in animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on organic minerals proved that chelate minerals can be more effectively absorbed in the intestines than inorganic oxide and sulfate (Wedekind et al 1992;Aoyagi and Baker 1993). Accordingly, chelated Fe, especially Fe-Gly, has been used more frequently as the Fe fortification in animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is well known that phytate seize positive charged metals and, consequently high phytate diets tend to confound the effects of the salt sources being tested. Zinc-methionine supplemented to cornsoybean meal diets presented 206% bioavailability, but only 117% when included in a purified diet without phytate (Wedekind et al, 1992). In all-vegetable feeds, which bear a high proportion of phytate, the advantage of mineral chelates tends to be easier observed as compared to diets with animal by-products inclusion.…”
Section: Performance Of Poultry Fed Chelated Mineralsmentioning
confidence: 99%
“…In addition, increased claw problems are observed in a Co deficiency due to decreased protein synthesis (Smart and Cymbaluk 1997). Amino acid complexes of trace minerals are more bioavailable (Wedekind et al 1992) and compared with sources result in similar outcome in lower amounts (Nocek et al 2006). Given that those causes were mentioned the improved claw integrity was expected.…”
Section: Lamenessmentioning
confidence: 99%
“…Brethour et al (1986) observed an 11.6% increase in ADG and 5.3% decrease in DM/gain by the addition of 10.5-g sodium bicarbonate per kilogram feed DM to wheat sorghum-based diets. Amino acid complexes of trace minerals are more bioavailable (Wedekind et al 1992) and are better retained by the body (Nockels et al 1993) than inorganic sources of trace minerals. This improved bioavailability may stimulate weight gain and feed conversion ratio in cattle (Kessler et al 2003).…”
Section: Adg and G:fmentioning
confidence: 99%
See 1 more Smart Citation